IMPACT OF MACRO-ECONOMIC VARIABLES ON STOCK MARKET CAPITALIZATION AND VOLATILITY: EVIDENCE FROM THE CAPITAL MARKET OF BANGLADESH - Md. Mehedi Hasan; Md. Hasan Uddin; Md. Alauddin (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This paper explores the factors affecting Stock Market Volatility (SMV) and Stock Market Capitalization (SMC) through Ordinary Least Squares (OLS) regression analysis from 2001 to 2022. The analysis indicates that trade volume and market return (MR) have a significant impact on SMV, while market capitalization, trade openness, and inflation do not show notable effects. In terms of SMC, trade openness and domestic credit to the private sector are identified as significant positive determinants. In contrast, gross fixed capital formation is found to have a negative relationship with SMC. These insights improve the understanding of stock market dynamics and could inform policy measures aimed at enhancing market stability and growth.